1976
DOI: 10.1073/pnas.73.11.4115
|View full text |Cite
|
Sign up to set email alerts
|

Direct method for detection and characterization of cell surface receptors for insulin by means of 125I-labeled autoantibodies against the insulin receptor.

Abstract: Autoantibodies directed against the cell surface receptors for insulin are found in some patients with extreme insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…We inquired whether the leftward shift of the binding-competition curves is specific for insulin and insulin analogs. In the case of antibodies to the insulin receptor, another ligand for the receptor (14), the leftward shift of the binding curve was not observed. Anti-receptor antibodies appeared to recognize insulin receptors equally well from all cell types studied (Fig.…”
Section: Introductionmentioning
confidence: 89%
“…We inquired whether the leftward shift of the binding-competition curves is specific for insulin and insulin analogs. In the case of antibodies to the insulin receptor, another ligand for the receptor (14), the leftward shift of the binding curve was not observed. Anti-receptor antibodies appeared to recognize insulin receptors equally well from all cell types studied (Fig.…”
Section: Introductionmentioning
confidence: 89%
“…Second, serum from patient B-7 and control serum were precipitated with ammonium sulfate (33% final concentration), the precipitate redissolved in phosphate buffer (0.01 M KH2PO4, pH 8), and dialyzed for 24 h in phosphate buffer, using dialysis tubing with a 3,500 D cutoff range. The retained material was concentrated and iodinated with 1251I using chloramine T oxidation to a final specific activity of 10-15 ,Ci/Mg protein as previously described by Jarrett et al (21). Additionally, the ammonium sulfate precipitates were further resolved on DEAE ion exchange chromatography according to the procedure of Jarrett et al (21).…”
Section: Heart Perfusion Andfixationmentioning
confidence: 99%
“…The retained material was concentrated and iodinated with 1251I using chloramine T oxidation to a final specific activity of 10-15 ,Ci/Mg protein as previously described by Jarrett et al (21). Additionally, the ammonium sulfate precipitates were further resolved on DEAE ion exchange chromatography according to the procedure of Jarrett et al (21). The DEAE-purified material was also concentrated, iodinated with '25I to a specific activity of - [10][11][12][13][14][15] ,MCi/Mg protein.…”
Section: Heart Perfusion Andfixationmentioning
confidence: 99%
“…In a previous report, we have shown that the circulating inhibitors in these patients are polyclonal immunoglobulins, primarily of the IgG class, and that their inhibitory activity is mediated through the F(ab')2 portion of the molecule (3). Further, several lines of evidence strongly suggest that these antibodies act by binding directly to determinants on, or intimately linked to, the insulin receptor molecule (2)(3)(4). Thus, these immunoglobulins may be considered to be "antireceptor antibodies" such as those which have been proposed as etiologic factors in Graves' disease (5) and myasthenia gravis (6).…”
Section: Introductionmentioning
confidence: 99%